A novel codrug made of the combination of ethionamide and its potentiating booster: synthesis, self-assembly into nanoparticles and antimycobacterial evaluation. Issue 20 (10th May 2019) - Pastor, Alexandra; Machelart, Arnaud; Li, Xue; Willand, Nicolas; Baulard, Alain; Brodin, Priscille; Gref, Ruxandra; Desmaële, Didier
Abstract : A self-assembling codrug of ethionamide with its booster induced reduction of the bacterial load in mycobacterium-infected mice upon intranasal administration. Abstract : Ethionamide (ETH) is one of the most widely used second-line chemotherapeutic drugs for the treatment of multi-drug-resistant tuberculosis. The bioactivation and activity of ETH is dramatically potentiated by a family of molecules called "boosters" among which BDM43266 is one of the most potent. However, the co-administration of these active molecules is hampered by their low solubility in biological media and by the strong tendency of ETH to crystallize. A novel strategy that involves synthesizing a codrug able to self-associate into nanoparticles prone to be taken up by infected macrophages is proposed here. This codrug is designed by tethering N -hydroxymethyl derivatives of both ETH and its booster through a glutaric linker. This codrug self-assembles into nanoparticles of around 200 nm, stable upon extreme dilution without disaggregating as well as upon concentration. The nanoparticles of the codrug can be intranasally administered overcoming the unfavorable physico-chemical profiles of the parent drugs. Intrapulmonary delivery of the codrug nanoparticles to Mtb infected mice via the intranasal route at days 7, 9, 11, 14, 16 and 18 post-infection reduces the bacterial load in the lungs by a factor of 6.